2020
DOI: 10.1177/1461444820959019
|View full text |Cite
|
Sign up to set email alerts
|

In(cel)doctrination: How technologically facilitated misogyny moves violence off screens and on to streets

Abstract: This qualitative study explores how technological affordances of the digital space, facilitate the anti-feminist discourses which characterise the digital community Incel (Involuntarily Celibates). The data in this article are drawn from a variety of sources, including video ethnography and an analysis of long-form interviews drawn from a year-long documentary project, to examine the experience of young men in Incel communities, and the process of indoctrination into misogynistic extremism. Results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 19 publications
0
35
0
2
Order By: Relevance
“…This was followed by Alek Minassian's van attack in Toronto in 2018, resulting in the deaths of 10 female victims and injury to another 16 (Williams 2021). It was later revealed that Minassian had hailed Elliot Rodger as his hero (Speckhard 2021) and explained that following Rodger's attack he felt proud and radicalised, stating that it was 'time to take action rather than fester in his own sadness' (Regehr 2022). Before the most recent incel-inspired mass shooting in Plymouth, Jake Davison blamed the blackpill philosophy for his increasing hopelessness that ultimately led to his killing spree (Townsend 2021).…”
Section: Incels Violence and Mental Illnessmentioning
confidence: 99%
“…This was followed by Alek Minassian's van attack in Toronto in 2018, resulting in the deaths of 10 female victims and injury to another 16 (Williams 2021). It was later revealed that Minassian had hailed Elliot Rodger as his hero (Speckhard 2021) and explained that following Rodger's attack he felt proud and radicalised, stating that it was 'time to take action rather than fester in his own sadness' (Regehr 2022). Before the most recent incel-inspired mass shooting in Plymouth, Jake Davison blamed the blackpill philosophy for his increasing hopelessness that ultimately led to his killing spree (Townsend 2021).…”
Section: Incels Violence and Mental Illnessmentioning
confidence: 99%
“…From the early 2000s, the internet expanded MRAs' capabilities to disseminate anti-feminist discourse publicly. During this time, groups continued to petition to recognise men as an oppressed classoppressed chiefly by feminists/ism-but also mirrored the grassroots activism of third-wave feminism (Dragiewicz 2011;Regehr 2020). MRA groups focused on shifting cultural attitudes through cyberactivism rather than attempting to influence law and policy decisions (Gotell and Dutton 2016).…”
Section: Tracing the Contemporary Anti-feminist Men's Movementsmentioning
confidence: 99%
“…In line with the results from the 2019 survey (SergeantIncel, 2019) which highlighted negative mental health among Incels.co users, several studies have reported on psychological and social issues prevalent among Incels. Expressions of loneliness, hopelessness and depression were observed in Incel forums (Chopite, 2022;Høiland, 2019;Jaki et al, 2019;Jones, 2020;Maxwell et al, 2020;Regehr, 2020;Rubertsson, 2019;Williams, 2020). A quarter (25%) of threads analyzed in one study contained ''it's over,'' reflecting users' lack of hope of escaping their predicament, a view also expressed by discussion of the blackpill (Jaki et al, 2019).…”
Section: Qualitative Studies Providing Psychosocial Data On Incelsmentioning
confidence: 99%